1983
DOI: 10.1038/bjc.1983.106
|View full text |Cite
|
Sign up to set email alerts
|

Characterisation of Epstein-Barr virus-specific memory T cells from the peripheral blood of seropositive individuals

Abstract: Epstein-Barr virus (EBV) is a B lymphotrophic human herpes virus which is the causative agent of Infectious Mononucleosis (IM) (Henle et al., 1968) and is aetiologically associated with Burkitt's lymphoma (Epstein & Achong, 1979) and nasopharyngeal carcinoma (Epstein, 1978). In most individuals infection occurs subclinically during childhood (Evans et al., 1968) and leads to the production of antibodies to virus-determined antigens which thereafter persist for life (Hewetson et al., 1973). Following either IM … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
7
0

Year Published

1984
1984
2015
2015

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(7 citation statements)
references
References 20 publications
0
7
0
Order By: Relevance
“…Most previous in vitro studies have monitored PBMC culture responses to EBV via a regression assay, in which the readout is microscopic enumeration of transformed-cell foci after 4 weeks in culture or isolation of transformed lymphoblastoid lines (37,40). As a quantitative and rapid assay for T-cell control, we initially assessed cell proliferation in EBV-infected and mock-inoculated PBMC cultures by measuring [ 3 H]dT incorporation 17 to 18 days after inoculation (13,26,33,55).…”
Section: Lack Of Memory T-cell Activity Augments Proliferation In Ebvmentioning
confidence: 99%
“…Most previous in vitro studies have monitored PBMC culture responses to EBV via a regression assay, in which the readout is microscopic enumeration of transformed-cell foci after 4 weeks in culture or isolation of transformed lymphoblastoid lines (37,40). As a quantitative and rapid assay for T-cell control, we initially assessed cell proliferation in EBV-infected and mock-inoculated PBMC cultures by measuring [ 3 H]dT incorporation 17 to 18 days after inoculation (13,26,33,55).…”
Section: Lack Of Memory T-cell Activity Augments Proliferation In Ebvmentioning
confidence: 99%
“…In countries such as Kenya, EBV infection generally occurs by 2 years of age [8][9][10][11] and persists for life as a latent infection in memory B cells [12]. The lytic phase of viral replication is thought to occur after plasma cell differentiation [13][14][15]. The virus is periodically shed in the saliva, suggesting that there is ongoing lytic-cycle reactivation [16].…”
mentioning
confidence: 99%
“…Much of the early literature using this system indicated that regression was associated with the appearance of EBV latent antigen-specific T cells that were operationally HLA class I-restricted in cytotoxicity assays on LCL targets (28,29,38,50) and were therefore assumed to be CD8 ϩ T cells. Indeed, the first experiments separating CD4 ϩ and CD8 ϩ T cells from PBMC cultures strongly supported this assumption (7). A more recent analysis using natural killer (NK) and T-cell subset depletions, however, suggested that CD4 ϩ T cells were the principal effectors of regression (33).…”
mentioning
confidence: 99%